2010
DOI: 10.5539/ibr.v3n2p136
|View full text |Cite
|
Sign up to set email alerts
|

Fertility, Health and Female Labour Force Participation in Urban Cameroon

Abstract: Many studies report empirical relationship either between fertility and labour supply or, between health and labour market outcomes. In this paper, an extension of these ideas involves explicitly considering how fertility and health affect each other, and how they interrelate with labour force participation. A unifying framework is provided and a simultaneous three equations model developed to capture the interdependence between these variables as well as their respective determinants. The model is estimated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…If a subject's fertility were to increase by one, the log-odds for being employed relative to not being employed would be expected to increase by 0.96 units holding other variables constant. This implies that contrary to the expectations that having children might disturb women from actively being involved in the labour market, this finding confirms that of Tsafack and Zamo-Akono (2010) who concluded that fertility has a positive impact on the probability of women's labour force participation. This can be justified by the fact that having many children have proven to place additional financial burden on the woman in particular and their family as a whole thus forcing the woman to work in order to gain extra income to provide for these children.…”
Section: Determinants Of Women's Employment In Cameroonsupporting
confidence: 62%
“…If a subject's fertility were to increase by one, the log-odds for being employed relative to not being employed would be expected to increase by 0.96 units holding other variables constant. This implies that contrary to the expectations that having children might disturb women from actively being involved in the labour market, this finding confirms that of Tsafack and Zamo-Akono (2010) who concluded that fertility has a positive impact on the probability of women's labour force participation. This can be justified by the fact that having many children have proven to place additional financial burden on the woman in particular and their family as a whole thus forcing the woman to work in order to gain extra income to provide for these children.…”
Section: Determinants Of Women's Employment In Cameroonsupporting
confidence: 62%
“…That is, as people live longer, they invest more in human capital, which, in turn, results in an increase in female labor participation and a reduction in the pay gap between genders. [5] use fertility, health and labor supply data to estimate the relationship between labor participation and fertility in Cameroon. Their results suggest a strong relationship between fertility and health conditions, and they not that engagement in the labor market decreases fertility rates, whereas having children increases the chances of female labor participation.…”
Section: Discussionmentioning
confidence: 99%
“…[3] , [4] analyze the trend in female labor supply using PNAD data for the 1970s, 1980s and 1990s. By modeling fertility, health and labor participation in Cameroon, [5] concluded that although labor participation reduces fertility rates, having a child increases a woman’s propensity to work. [6] use evidence from different countries throughout the world to motivate a theoretical model that suggests that the increase in labor participation was motivated by the decline in wage discrimination against women and that the reduction in child mortality reduced fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Physical disabilities: Of five studies addressing the impacts of physical disabilities, Bremer et al [ 38 ], Fernande and Paul-Iva [ 39 ] and Kiani [ 40 ] addressed participation restrictions for people living with mobility impairments (PLWMI). Kiani [ 40 ], Nanfosso and Zamo-Akono [ 41 ] and Zamo-Akono [ 42 ] addressed employment restrictions. All five studies found that having a physical disability made it difficult to participate in employment [ 38 – 42 ].…”
Section: Resultsmentioning
confidence: 99%